Intersections in simulation and gaming : disruption and balance : Third Australasian Simulation Congress, ASC 2019, Gold Coast, Australia, September 2-5, 2019 : proceedings /: disruption and balance : Third Australasian Simulation Congress, ASC 2019, Gold Coast, Australia, September 2-5, 2019 : proceedings. ([2019]) - Unknown
No abstract available